Study of health resource and health outcomes: Organization of economic corporation and development panel data analysis - Seyede Sedighe Hosseini Jebeli; Mohammad Hadian; Aghdas Souresrafil (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: There are numerous factors which affect the health status in different ways, including financing mechanisms, health-care expenditures, socioeconomic characteristics, and health-care resources. One of the most important factors which contribute to the health status of a population is health-care resource which includes number of beds or health-care professionals for instance. AIMS: The objectives of this study were as follows: to examine the regression of the life expectancy and health-care inputs and also to investigate the regression of death rate and health-care inputs. SETTINGS AND DESIGN: This study was a panel dataset analysis of OECD countries. MATERIALS AND METHODS: A generalized method of moment (GMM) regression models with country-level health outcomes (death rate and life expectancy) as dependent variables were estimated. A panel dataset with n = 26 (the number of countries) and T = 12 (the number of time periods) was used. The GMM regression model was used to estimate the effect of health-care resources on health outcomes. RESULTS: Findings showed that there are strong reverse correlations between immunization rate and number of physicians with crude rate of death (−2.64 [P < 001] and −76.50 [P < 001], respectively). There were also positive correlations between immunization rate and number of physicians with life expectancy at birth (0.01 [P < 001] and 1.03 [P < 001], respectively). Moreover, there were negative correlations between inpatient rate and beds with life expectancy (−0.00003 [P < 001] and −0.12 [P < 001], respectively). CONCLUSIONS: It is essential for policymakers to consider the optimal level of health resource to achieve better health outcomes. Oversupply of hospital beds and specialist doctors could lead to induced demand and put the patients at risk of unnecessary procedures.